Entrepreneurial knowledge, skills, competencies and performance: A study of micro-enterprises in Kelantan, Malaysia. Issue 1 (15th April 2019) - Al Mamun, Abdullah; Fazal, Syed Ali; Muniady, Rajennd
Abstract : Purpose: This study aims to examine the effect of entrepreneurial skills, market orientation, sales orientations and networking on entrepreneurial competency and performance of micro-enterprises in Kelantan, Malaysia. Design/methodology/approach: Adopting a cross-sectional design, this paper collected data through structured interviews from 403 micro-entrepreneurs from "Majlis Amanah Rakyat, " Kelantan and "Majlis Agama Islam dan Adat Istiadat, " Kelantan. Findings: The findings reveal that entrepreneurial skills, market orientation and networking have a positive effect on entrepreneurial competency. Then, entrepreneurial competency, entrepreneurial skills and networking have a positive effect on enterprise performance. The findings show a significant mediation effect of entrepreneurial competency on the relationships between entrepreneurial skills, market orientation and networking and enterprise performance. Originality/value: Addressing the understudied "human factor" in entrepreneurship, this paper extends the resource-based view and enriches the existing entrepreneurship literature in Malaysia. It provides useful insights into the improvement of micro-enterprise performance, which is crucial for promoting entrepreneurial activities and for enhancing socio-economic conditions among low-income households in Malaysia. Thus, the government and developmental organizations should focus on the development of entrepreneurial skills, market-oriented approach, networking traits and entrepreneurial competencies and subsequently encourage poor households to perform entrepreneurial activities.